2007
DOI: 10.1002/jat.1193
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of acute toxicity of fenitrothion on guppies Poecilia reticulata

Abstract: Fenitrothion, an organophosphothionate insecticide (CAS number: 122-14-5) and potential toxic pollutant contaminating aquatic ecosystems, was investigated in the present study for acute toxicity. Guppy fish (Poecilia reticulata) were selected for the bioassay experiments. The experiments were repeated three times and the 96 h LC(50) was determined for the guppies. The static test method of acute toxicity test was used. The water temperature was regulated at 23 +/- 1 degrees C. In addition, behavioral changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Our studies for acute fenitrothion toxicity with freshwater fish, guppy (Poecilia reticulata), showed 96-h LC 50 value to be 3.28 mg/L [25]; peppered corydoras (Corydoras paleatus) showed 96-h LC 50 value to be 3.51 mg/L [26]; and tilapia (Oreochromis niloticus) larvae and fry showed 96-h LC 50 values to be 0.72 and 0.07 mg/L, respectively [27].…”
Section: Statistical Proceduresmentioning
confidence: 96%
“…Our studies for acute fenitrothion toxicity with freshwater fish, guppy (Poecilia reticulata), showed 96-h LC 50 value to be 3.28 mg/L [25]; peppered corydoras (Corydoras paleatus) showed 96-h LC 50 value to be 3.51 mg/L [26]; and tilapia (Oreochromis niloticus) larvae and fry showed 96-h LC 50 values to be 0.72 and 0.07 mg/L, respectively [27].…”
Section: Statistical Proceduresmentioning
confidence: 96%
“…Several studies have observed behavioural responses of fish, including loss of equilibrium, spiral swimming, rapid gill movement, staying motionless etc. due to sumithion exposure beyond the threshold level (Sancho et al 1998a;Sancho et al 1998b;Sarikaya et al 2004;Sarikaya et al 2007;Benli & € Ozkul 2010). The concentration of sumithion for behavioural changes in fish varies among species.…”
Section: Lethal Concentrations Of Sumithion For Fishmentioning
confidence: 99%
“…2004; Sarikaya et al . 2007; Benli & Özkul 2010). The concentration of sumithion for behavioural changes in fish varies among species.…”
Section: Lethal Concentrations Of Sumithion For Fishmentioning
confidence: 99%
“…They have various combinations of colour patterns especially on the sides of the body and fins (Froese & Pauly, 2018). P. reticulata has several roles and benefits in life, including predators of several disease-causing mosquito larvae (Saleeza et al, 2014), used as ornamental aquarium fish (Singh et al, 2010), and act as an indicator of quality in the aquatic environments (Sarikaya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%